Irrational to expect low risk and high returns - KOH, Benedict (Institutional Knowledge at Singapore Management University, 2014)
The low interest paid on Central Provident Fund (CPF) balances when compared with the relatively high returns earned by government investment entities such as Temasek Holdings and GIG is a common gripe.